ตอบ:
#abs z <1 #
คำอธิบาย:
# d / (dz) (z-1 / 2z ^ 2 + 1 / 3z ^ 3 + cdots + (- 1) ^ (n + 1) / nz ^ n + cdots) = sum_ (k = 0) ^ oo (-1) ^ ^ KZ k #
แต่
#sum_ (k = 0) ^ oo (-1) ^ k z ^ k = lim_ (n-> oo) (z ^ n + 1) / (z + 1) #. กำลังพิจารณา #abs z <1 # เรามี
#sum_ (k = 0) ^ oo (-1) ^ k z ^ k = 1 / (1 + z) # และ
#int sum_ (k = 0) ^ oo (-1) ^ kz ^ k dz = บันทึก (1 + z) #
ตอนนี้การทดแทน #Z -> - Z # เรามี
# -int sum_ (k = 0) ^ oo z ^ k dz = -sum_ (k = 1) ^ oo z ^ k / k = บันทึก (1-z) #
ดังนั้นมันจึงมาบรรจบกัน #abs z <1 #